The Las Pinas-Paranaque critical habitat and ecotourism area wetland biodiversity complex - Areja, Candy Abigail J.
The Las Pinas-Paranque Critical Habitat and Ecotourism Area (LPPCHEA) is the last remaining wetland in Manila bay and the first critical habitat established in the country by a virtue of a Presidential Proclamation. It was established to protect the critical habitat's rich biodiversity and wetland ecosystem from the continuous degradations seen in the past decades. However, most of the people are not aware of its existence and importance. This resent situation could lead to lack of appreciation and apathy, to complete ignorance of the area and its conservation. As architecture presumes to be influential in the field of tourism, architectural solutions can be introduced to effectively catch the attention and interest of the society. Through architecture, tourism in the area can be established while advocating the principles of ecotourism. Thus, this project endeavors to provide a dynamic and captivating design that fulfills the expectations of the tourists who have come to experience a unique wildlife setting right in the heart of the metropolis. At the same time, it encourages behavior change towards nature conservation and minimizes negative environmental impacts to avoid further destruction and aid in the restoration and conservation of the already degraded environment of LPPCHEA.